IMPLEMENTASI SDG’S MELALUI OPTIMALISASI SALURAN SANITASI DAN SIRKULASI AIR WADUK JATIBARANG MENUJU MASYARAKAT BERDAYA - Adinda Mei Erawati; Churun A’in; Azka Daysa; Tegar Yuniarto; Rendi Hermawan Pradekso; Endah Rahmawati Permatasari (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Sustainable Development Goals (SDGs) are 17 points of collective agreement produced at the 70th session of the United Nations (UN) in New York, United States. The sixth SDGs point aims at "Clean Water and Adequate Sanitation". The main problem of circulation and sanitation of the Jatibarang Reservoir is frequent flooding and contamination of clean water for community needs. The purpose of community service activities is to implement SDGs point 6 and strive to realize community welfare. All activities related to optimizing circulation and repairing water sanitation channels implement the community approach method first, followed by analyzing the problems and potential solutions needed through the channel condition survey process, then applying observation and documentation methods that are implemented in repair activities and testing the results of repairing sanitation channels and water circulation in Jatibarang Reservoir. Repair and optimization of circulation and sanitation channels of Jatibarang Reservoir water in the context of community empowerment are guided by the rules of proper sanitation channel repair, so as to realize goal number 6 of the SDG's, namely access to clean water and proper sanitation. Proper sanitation channels and water circulation include differentiating waste water channels with toilet waste, improving sanitation facilities with structured suitability, there are efforts to control pollution (through the improvement of control basins and gradual filtration systems), presence of water catchment areas, and periodic channel monitoring access